Analysis of Land Value in the Area Surrounding the Central Business District (CBD) of Simpang Lima, Semarang City Using Geographically Weighted Regression (GWR) - Fauzi Janu Amarrohman; Yasser Wahyuddin; Ellena Patricia (Journal of Applied Geospatial Information, 2023)
According to the Regional Spatial Plan (RTRW) for the City of Semarang in 2011–2031, the area around Simpang Lima is part of City Area 1, with a function as the Central Business District (CBD). Losch (1954) suggests that the value of a parcel of land tends to decrease if it is away from the central business area. Therefore, this study investigated the relationship between changes in land value and the presence of CBD around the Simpang Lima CBD. The methods employed in this study are the calculation of the Average Indicated Value (NIR), analyzing changes in land value in 2012–2023, and the Geographically Weighted Regression (GWR). Based on an analysis of changes in land value for 2012–2023, it shows that the highest change in land value zone for 2012–2018 was in zone 166, with an increase of IDR 20,446,000, and the lowest change in land value was in zone 163, with a decrease of IDR 3,956,000. Meanwhile, the highest change in land value zone for 2018–2023 was in zone 84, with an increase of IDR 28,852,000, and the lowest change in land value was in zone 37, with an increase of IDR 217,000. The results of statistical tests using GWR show that the influence of the distance from the CBD on changes in land values in 2012–2023 is 84%, indicating a high correlation. The results of the T-test performed on each variable indicate that the variables significantly influencing changes in land value are shopping centers and road widths. Shopping centers have a negative correlation. On the other hand, the road width is positively correlation.